Pengembangan E-Modul Praktikum Eubacteria pada Kelas X SMAN 3 Kefamenanu - Oki, Gres Adelina Novanda; Sila, Vinsensia Ulia Rita; Masing, Feliksitas Angel (BIO-EDU: Jurnal Pendidikan Biologi, 2024)
For this reason, this research aims: 1) To develop Eubacteria practicum E-module in class X SMAN 3 Kefamenanu, 2) To determine the feasibility of Eubacteria practicum E-module in class X SMAN 3 Kefamenanu. This research uses the Research and Development (R&D) method using 3 important stages consisting of: 1) Preliminary study 2) model development stage, 3) evaluation or testing stage. Data was obtained from material expert validation and media expert validation, then trials to Biology subject teachers and students. Trials to two teachers of Biology subjects as respondents and trials to students consisted of limited trials or groups of 5 students and small group trials of 20 students. The results of this development research are as follows: 1) Eubacteria practicum E-module which was developed into teaching materials that are suitable for use by Biology subject teachers and students of SMAN 3 Kefamenanu, 2) E-modules are declared suitable for use as teaching materials with data obtained from 95.00% material expert validation and 91.57% media expert validation with eligibility criteria declared very suitable for use as teaching materials. Based on validation from material experts and media experts, then the Eubacteria practicum E-module was tested on teachers of Biology subjects and students of SMAN 3 Kefamenanu. The results of the trial of Biology subject teachers on respondent 1 with a percentage of 96.00%, while the percentage of respondent 2 was 92.00%. The results of the trial were limited to 88.40%, while the small group trial was 87.10%. Thus, the results of trials for teachers of Biology subjects and students of grade X SMAN 3 Kefamenanu were declared very suitable for use as teaching materials.